Internship Experience and Locus of Control as Determinants of Work Readiness among Internship Program Participants - Ika Nur Auliani; Khaerul Rizal Abdurahman (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2026)
Work readiness among internship program participants is an important indicator in meeting professional workforce demands. Preliminary observations at PT Bio Farma (Persero) revealed differences in work readiness influenced by internship experience and internal psychological factors such as locus of control. Internship experience provides opportunities to apply theoretical knowledge in real workplace settings, while locus of control reflects an individual’s belief that outcomes are shaped by personal ability and competence. This study aims to examine the effects of internship experience and locus of control on the work readiness of internship participants at PT Bio Farma (Persero). A quantitative approach was employed, and data were collected from 52 bachelor’s degree internship participants. Multiple linear regression was used to test partial relationships, whereas the simultaneous contribution of the variables was evaluated using the coefficient of determination (R²). The results indicate that internship experience and locus of control have a positive and significant influence on work readiness, both individually and jointly. These findings highlight the importance of meaningful workplace learning experiences and strengthening interns’ confidence in their own capabilities. The study provides managerial implications for organizations in designing internship programs that better prepare participants for professional careers.